The Pattern of Social Parasitism in Maculinea teleius Butterfly Is Driven by the Size and Spatial Distribution of the Host Ant Nests - Magdalena Witek; Valentina La Morgia; Luca Pietro Casacci; Francesca Barbero (Insects, 2023)
The parasitic relationship between Maculinea butterflies and Myrmica ants has been extensively studied but little information is available on the spatial occurrence of Maculinea larvae. We searched for the presence of Maculinea teleius in 211 ant nests at two sites in two crucial phases of its life cycle, i.e., in autumn, during the initial larval development, and in the following late spring, before pupation. We assessed variations in the proportion of infested nests and factors correlated with spatial distributions of parasites in Myrmica colonies. The parasitism rate in autumn was very high (∼50% of infestation rate) but decreased in the following spring. The most important factor explaining parasite occurrence in both seasons was the nest size. Further factors, such as the presence of other parasites, the Myrmica species or the site, concurred to explain the differential survival of Ma. teleius until the final development. Irrespective of the host nest distribution, the parasite distribution changed from even in autumn to clumped in late spring. Our work showed that the survival of Ma. teleius is correlated with colony features but also with the nest spatial distribution, which therefore should be taken into consideration in conservation strategies aiming at preserving these endangered species.